Kualitas Air Sungai Di Sekitar Pltu Sintang Kalimantan Barat - Iqbal, Muhammad; Diba, Farah; Gusmayanti, Evi (Universitas Tanjungpura, 2025)
The Kapar River is the recipient of waste discharge from the Sintang PLTU Industry, while the Kapuas River is the estuary of the Kapar River. The area around the Sintang PLTU Industry is the location of the Sintang Regency Industrial Area as the impact of establishing this area could affect the level of water quality. This research aims to determine the water quality of the Kapar River and Kapuas River due to the existence of the Sintang PLTU Industry. This research use the Pollution Index (IP) method. The research results show that the water quality condition of the Kapar River using the Pollution Index method is Lightly Polluted. The Kapar River is in the Pollution Index range of around 0.36